Edge- and surface-emitting 10.1 μm quantum cascade distributed feedback lasers - Hofstetter, Daniel; Faist, Jérôme; Beck, Mattias; Müller, Antoine; Oesterle, Ursula (My University, 2000)
We present measurement results on high-power low-threshold quantum cascade-distributed feedback lasers emitting infrared radiation at 10.16 μm. A lateral current injection scheme allowed the use of a strongly coupled surface grating without metal coverage and epitaxial re-growth. Although this design resulted in a simplified processing, the fabrication of high-performance edge- and surface-emitting devices was demonstrated. For the edge-emitting laser, we used a standard first-order grating with a period of 1.57 μm, and for the surface emitter, a second-order grating with a period of 3.15 μm was used. Maximal output powers in excess of 200 mW at 85 K and 70 mW at 300 K were achieved for both configurations. The threshold current densities at 85 K (300 K) were 1.85 kA/cm2 (5.4 kA/cm2) and 2.1 kA/cm2 (5.6 kA/cm2) for edge and surface emitters, respectively.
Keywords: Quantum cascade lasers; Distributed feedback lasers; Surface emission; Lateral current injection